2011
DOI: 10.1038/ncomms1608
|View full text |Cite
|
Sign up to set email alerts
|

Competition for FcRn-mediated transport gives rise to short half-life of human IgG3 and offers therapeutic potential

Abstract: Human IgG3 displays the strongest effector functions of all IgG subclasses but has a short half-life for unresolved reasons. Here we show that IgG3 binds to IgG-salvage receptor (FcRn), but that FcRn-mediated transport and rescue of IgG3 is inhibited in the presence of IgG1 due to intracellular competition between IgG1 and IgG3. We reveal that this occurs because of a single amino acid difference at position 435, where IgG3 has an arginine instead of the histidine found in all other IgG subclasses. While the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
286
3
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 243 publications
(300 citation statements)
references
References 53 publications
9
286
3
2
Order By: Relevance
“…Still, recent reports identified a competition between IgG subtypes in the early endosome to be responsible for the short serum half-life of IgG3 [6]. This is due to an arginine at position 435 in IgG3 instead of histidine as in other IgG subtypes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Still, recent reports identified a competition between IgG subtypes in the early endosome to be responsible for the short serum half-life of IgG3 [6]. This is due to an arginine at position 435 in IgG3 instead of histidine as in other IgG subtypes.…”
Section: Discussionmentioning
confidence: 98%
“…It has been recognized recently that binding to FcRn at low pH and dissociation from FcRn at neutral pH appear to be critical for the reported long FcRn-dependent serum halflife of IgG-type antibodies [4][5][6]. Since both events are critical components of the FcRnIgG interaction, they should be included in a comprehensive analytical strategy as part of the candidate selection, quality control of therapeutic monoclonal antibodies (mAbs) or during quality by design studies [7][8][9].…”
mentioning
confidence: 99%
“…[37][38][39] Similarly, hIgG3 has been found highly efficient in protecting against pneumococcal infections in vivo, also through complement. 40,41 hIgG2 has a comparable binding pattern for the mouse Fc receptors as mIgG1, but with an estimated 5-to 50-fold lower affinity than mIgG1. This is in agreement with the results found by Overdijk et al, who showed hIgG2 to compete moderately with mIgG1 binding for mFcgRIIb and mFcgRIV.…”
Section: Discussionmentioning
confidence: 99%
“…97 The shorter serum half-life of IgG3 can be rescued by the introduction of the R435H mutation, resulting in a potent mAb for CDC. 98 IgG1/IgG3 chimera targeting CD20 showed stronger C1q binding, increased CDC capacity and more efficient B cell depletion in cynomolgus monkeys compared with the isotypematched parental mAbs. 99 Antibody amino-acid engineering influencing the binding of C1q to the Fc of an antibody can enhance complement activation.…”
Section: Inhibition Of Complement Regulatorsmentioning
confidence: 99%